The Effect Of Pop Up Book Media On Student Learning Outcomes In Ppkn Learning In Grade IV - H. Russel; Eva Pasaribu; Nancy Angelia Purba (Jurnal Pendidikan, Sains Sosial, dan Agama, 2023)
This study aims to determine the effect of Pop Up Book media on student learning outcomes in PPKN learning for grade IV of UPTD SD Negeri 122345 Jl.Thamrin Pematangsiantar. This study uses a One-Group Pretest-Posttest Design research design. The pretest was conducted to see students' abilities before being given treatment and the posttest was conducted to see students' abilities after being given treatment. The population in this study were all fourth-grade students at UPTD SD Negeri 122345 Jl.Thamrin Pematangsiantar and the sample used was 26 students at UPTD SD Negeri 122345 Pematangsiantar. The sampling technique used was Total sampling with two research variables, namely the dependent variable in the form of student learning outcomes, and the independent variable in the form of pop up book media. The results of hypothesis testing using paired sample t-test techniques with the help of the SPSS Version 21 program, based on the calculation results that the t-count value obtained is 18.715 with a sig. value of 0.000. The t-table value of the research data with many samples or N = 26, can then be calculated df / dk = 26-2 = 24. With a level of 0.063, the t-table value with a level of 0.025 is 2.063. From the calculation results obtained, it shows that the t-count value of 18.715> t-table value of 2.063 and a significance value of 0.00 <0.05. So it can be concluded that in the t-test there is a significant influence between Pop-up book Media on learning outcomes. From the results of the t-test above, we can see that Ha is accepted and Ho is rejected. This means that there is an influence of Pop-Up Books on student learning outcomes in PPKN learning at UPTD SD Negeri 122345 Jll. Thamrin Pematangsiantar.